Parámetros genéticos para características de crecimiento, canal, calidad y espinas intramusculares en cachama blanca (Piaractus brachypomus) (2019)
The topics of aquaculture in which innovation and research are re-quired are directed towards the improvement and genetic knowledge of native species. In this sense the present study concentrated on the estimation of heritabilities, genetic and phenotypic correlations for growth, carcass, quality and right intramuscular spines (RIMS) in white cachama (Piaractus brachypomus). The progeny of 12 females and 24 males by artificial fertilization of a female by two males, that is to say twelve half-sib families, were analyzed by means of the sta-tistical package SAS 9.4 (SAS®, 2014), assumed an univariate general linear model with inclusion of Fixed effects such as environmental factors, pond and age as fixed effects and genetic factors as random effects. Heritabilities in general for growth variables showed medi-um to high values; for carcass variables, presented low to medium values; And for the quality variables were low; For the RIMS the magnitude of the estimate was 0,11 ± 0,15. The correlations were generally close to unity between growth characteristics. These were significantly positive for body weight at 180 days of age with most variables unlike quality variables; the correlation for channel perfor-mance with RIMS of -0.99 was found to be significantly negative. The results of the study highlight the potential to improve growth, carcass and quality traits through the exploitation of the additive genetic variation observed in this study.